2013
DOI: 10.1002/jbm.a.35035
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical modulation of chitosan‐based hydrogels induces different biological responses: Interest for tissue engineering

Abstract: Polysaccharide-based hydrogels are remarkable materials for the development of tissue engineering strategies as they meet several critical requirements for such applications and they may partly mimic the extracellular matrix. Chitosan is widely envisioned as hydrogel in biomedical fields for its bioresorbability, biocompatibility, and fungistatic and bacteriostatic properties. In this study, we report that the modulation of the polymer concentration, the degree of acetylation, the gelation processes [or neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 35 publications
1
50
0
1
Order By: Relevance
“…Depending on the nature of the solvent and the chitosan's fraction of acetylated units, different gel morphologies can be obtained with different biological response. In a study by Rami et al, it was shown that soft and easily degraded gels manufactured from a highly acetylated chitosan were not suitable for culture of human mesenchymal stem cells, whereas a highly deacetylated chitosan following the same processing route gave rise to more solid gels with improved cell adhesion ( Figure 3) [22].…”
Section: Chitosan Physical Gelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on the nature of the solvent and the chitosan's fraction of acetylated units, different gel morphologies can be obtained with different biological response. In a study by Rami et al, it was shown that soft and easily degraded gels manufactured from a highly acetylated chitosan were not suitable for culture of human mesenchymal stem cells, whereas a highly deacetylated chitosan following the same processing route gave rise to more solid gels with improved cell adhesion ( Figure 3) [22].…”
Section: Chitosan Physical Gelsmentioning
confidence: 99%
“…Chitosan based hydrogels are of interest in tissue engineering applications, as they have good biocompatibility, are biodegradable in vivo, are low-toxic and non-immunogenic, and have tunable gel properties [39]. Additionally, and rather uniquely, chitosan gels are cationic and are able to interact with structural molecules such as glycosaminoglycans and glycoproteins present in the extracellular matrix [22,39], or indeed with other anionic biopolymers to form mixed biopolymer scaffolds to optimize either the mechanical or biological properties of the biomaterial [40]. Most chitosan scaffolds for tissue engineering are of this mixed type [10].…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Le chitosane est ainsi largement utilisé comme hydrogel dans le domaine biomédical pour sa biorésorbabi-lité, sa biocompatibilité et son pouvoir bactériosta-tique. Les paramètres comme la masse molaire, la concentration en polymère, le degré d'acétylation, le processus de gélification dans la préparation de différents hydrogels à base de chitosane, conduisent à des réponses biologiques différentes [24]. Les hydrogels physiques préparés à partir de chitosane hautement acétylés sont en effet dégradés rapidement in vivo, et ne conviennent pas à la culture in vitro de cellules souches mésenchymateuses humaines ou de cellules endothéliales dérivées de leurs progéniteurs circulants [25].…”
Section: Régénération Vasculaireunclassified